Healthy Kids Cambodia – A novel approach to triage for dental care in a population with extreme caries experience. Issue 1 (17th November 2019) - Turton, Bathsheba; Patel, Jilen; Hill, Rachel; Sieng, Chanthyda; Durward, Callum
Abstract: Objectives: To describe the disease experiences and treatment provided according to a set of novel triage criteria among children in the Healthy Kids Cambodia project. Methods: The present study describes the management of caries using the Healthy Kids Cambodia (HKC) strategy at one school in Phnom Penh, Cambodia. Treatment was provided across three levels of care based on a set of simple screening criteria. All children received Level 1 (L1) care, which included application of 30% silver diammine fluoride (SDF) to arrest dental caries. Level 2 (L2) care involved use of atraumatic restorative treatment (ART) and GIC fissure sealants for children between six and eight years of age, and for older children who had one or more cavitated lesions on permanent posterior teeth. Level 3 care involved conventional dental rehabilitation for those children with cavitated lesions in permanent anterior teeth, acute infections, pulpally involved permanent teeth or carious permanent posterior teeth that were not restorable using ART. Three activities were evaluated: (i) screening of all children at the school using the HKC triage criteria; (ii) a detailed re‐examination of children in Grades 3 and 4; and (iii) a clinical audit of treatment provided at Level 3 (L3). Results: 1194 children were screened using the HKC approach, and a sample of 304 8‐ to 12‐year‐old children was re‐examined. Among those who were re‐examined, 48 (15.7%) had been referred for L3 treatment and 88 (28.9%) referred for L2 (only). There was a significant difference in baseline caries experience by referral level, whereby those referred to higher levels of care had more severe caries experience. All children in the L3 category required advanced rehabilitative care. Conclusions: The application of a triage system by dental students was successful in identifying children in greatest need of complex care (L3). Further research may better validate the system for caries management.